Characteristics of an ideal practice educator: Perspectives from undergraduate students in diagnostic radiography, nuclear medicine, nutrition and dietetics, occupational therapy, physiotherapy and radiation therapy. Issue 4 (November 2016) - Perram, A.; Hills, C.; Johnston, C.; MacDonald-Wicks, L.; Surjan, Y.; James, D.; Warren-Forward, H.
Abstract: Background: Practice education is a core component of undergraduate health programs, with the characteristics of the practice educator reported to have an influence on student experience during practical. This study analyses Australian student perceptions from six allied health professional undergraduate programs, to identify the characteristics of the ideal practice educator leading to successful placement experiences. Methods: An existing survey developed for medical students was modified to incorporate both quantitative and qualitative responses. Participants included all students enrolled in six undergraduate health professions in the School of Health Sciences at the University of Newcastle, Australia (n = 1485). Students were invited to complete the survey via hard copy or online. Results: There was a 54% response rate. The most valued characteristics were non-judgemental, clarity and feedback. The three least valued characteristics were scholarly activity, role model and practices evidence base practice. Students identified the importance of their relationship (respectful, inspirational and supportive) with the practice educator as being fundamental to a productive placement. Conclusion: The characteristics identified by respondents were common to all six professions, with little differences between gender, year of program or number of placements completed. This study suggests that the attitude of the practice educator towards the student is one of the key factors that underpin the success of practice experience across allied health professions. Highlights: The most important characteristics were non-judgmental and clarity . The least important characteristics were scholarly activity and being a role model . Female students valued all characteristics except being a role model as being more important. Participants older than 30 years valued being " available ", " aware " and " well prepared " more than the younger participants. High level of agreement in most and least favourable characteristics across disciplines.